Hemispheric asymmetry of the structure of dayside auroral oval. Issue 24 (16th December 2014) - Hu, Ze‐Jun; Ebihara, Yusuke; Yang, Hui‐Gen; Hu, Hong‐Qiao; Zhang, Bei‐Chen; Ni, Binbin; Shi, Run; Trondsen, Trond S.
Abstract A comprehensive analysis of long‐term and multispectral auroral observations made in the Arctic and Antarctica demonstrates that the dayside auroral ovals in two hemispheres are both presented in a two‐peak structure, namely, the prenoon 09:00 magnetic local time (MLT) and postnoon 15:00 MLT peaks. The two‐peak structures of dayside ovals, however, are asymmetric in the two hemispheres; i.e., the postnoon average auroral intensity is more than the prenoon one in the Northern Hemisphere but less in the Southern Hemisphere. The hemispheric asymmetry cannot be accounted for by the effect of the interplanetary magnetic field By component and the seasonal difference of ionospheric conductivities in the two hemispheres, which were used to interpret satellite‐observed real‐time auroral intensity asymmetries in the two hemispheres in previous studies. We suggest that the hemispheric asymmetry is the combined effect of the prenoon‐postnoon variations of the magnetosheath density and local ionospheric conductivity.